2019
DOI: 10.1093/cvr/cvz006
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib-induced cardiotoxicity: delineating the signalling mechanisms and potential rescue strategies

Abstract: Tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of chronic myelogenous leukaemia (CML). However, cardiotoxicity of these agents remains a serious concern. The underlying mechanism of these adverse cardiac effects is largely unknown. Delineation of the underlying mechanisms of TKIs associated cardiac dysfunction could guide potential prevention strategies, rescue approaches, and future drug design. This study aimed to determine the cardiotoxic potential of approved CML TKIs, define the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 73 publications
6
50
0
1
Order By: Relevance
“…A second hypothesis would link ponatinib-induced cell necrosis to Akt inhibition. Indeed, Akt is also highly implicated in the regulation of apoptosis signaling and mediates the responses of a majority of growth factors ( Somanath et al., 2006 ), and ponatinib is known to inhibit Akt in cardiomyocytes ( Singh et al., 2019 ). These observations highlight the need of a further thorough evaluation of this pathways in the endothelial response to ponatinib.…”
Section: Discussionmentioning
confidence: 99%
“…A second hypothesis would link ponatinib-induced cell necrosis to Akt inhibition. Indeed, Akt is also highly implicated in the regulation of apoptosis signaling and mediates the responses of a majority of growth factors ( Somanath et al., 2006 ), and ponatinib is known to inhibit Akt in cardiomyocytes ( Singh et al., 2019 ). These observations highlight the need of a further thorough evaluation of this pathways in the endothelial response to ponatinib.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cardiomyocytes necrosis was observed during high-dose sorafenib treatment with unclear mechanism (Duran et al, 2014). The most recent study reported that ponatinib inhibited phosphorylation of Akt and ERK1/2, which contributed to the activation of pro-apoptotic caspase-3 (Singh et al, 2019). Xu et al (2018) found that dasatinib dose-dependently up-regulated intracellular HMGB1 to induce cardiomyocyte necroptosis.…”
Section: Trastuzumabmentioning
confidence: 99%
“…One recent study evaluating the cardiotoxicity associated with ponatinib and potential rescue methods in zebrafish and isolated neonatal rat cardiomyocytes showed that ponatinib inhibits the essential cardiomyocyte prosurvival AKT/ERK signaling pathway, resulting in cardiomyocyte apoptosis [43]. Neuregulin-1β treatment prevented ponatinib-induced cardiotoxicity by supplementing this signaling pathway [45].…”
Section: Safety Profilementioning
confidence: 99%